Azobenzene-Based Solar Thermal Fuels: A Review - Zhang, Bo; Feng, Yiyu; Feng, Wei (Nano-Micro Letters, 2022)
The energy storage mechanism of azobenzene is based on the transformation of molecular cis and trans isomerization, while NBD/QC, DHA/VHF, and fulvalene dimetal complexes realize the energy storage function by changing the molecular structure. Acting as “molecular batteries,” they can exhibit excellent charging and discharging behavior by converting between trans and cis isomers or changing molecular structure upon absorption of ultraviolet light. Key properties determining the performance of STFs are stored energy, energy density, half-life, and solar energy conversion efficiency. This review is aiming to provide a comprehensive and authoritative overview on the recent advancements of azobenzene molecular photoswitch system in STFs fields, including derivatives and carbon nano-templates, which is emphasized for its attractive performance. Although the energy storage performance of Azo-STFs has already reached the level of commercial lithium batteries, the cycling capability and controllable release of energy still need to be further explored. For this, some potential solutions to the cycle performance are proposed, and the methods of azobenzene controllable energy release are summarized. Moreover, energy stored by STFs can be released in the form of mechanical energy, which in turn can also promote the release of thermal energy from STFs, implying that there could be a relationship between mechanical and thermal energy in Azo-STFs, providing a potential direction for further research on Azo-STFs. Highlights: 1 The strategy to achieve alternate mixing exotherm through metal–organic frameworks material that may be proposed to solve the potential drawbacks of azobenzene with nanocarbon template is discussed. 2 Factors that can affect the isomerization of the Azo unit include but are not limited to light, heat, catalysts, solvents, electric field, magnetic field, force were discussed to achieve controllable azobenzene energy release.